Diagnosis and Management of Bacterial Vaginosis: Summary of Evidence Reviewed for the 2021 Centers for Disease Control and Prevention Sexually Transmitted Infections Treatment Guidelines. (13th April 2022) - Muzny, Christina A; Balkus, Jennifer; Mitchell, Caroline; Sobel, Jack D; Workowski, Kimberly; Marrazzo, Jeanne; Schwebke, Jane R
Abstract: In preparation for the 2021 Centers for Disease Control and Prevention (CDC) sexually transmitted infections (STIs) treatment guidelines, the CDC convened an advisory group in 2019 to examine recent literature addressing updates in the epidemiology, diagnosis, and management of STIs. This article summarizes recent data in each of these key topic areas as they pertain to bacterial vaginosis (BV), the most common cause of vaginal discharge. The evidence reviewed primarily focused on updates in the global epidemiology of BV, risk factors for BV, data supportive of sexual transmission of BV-associated bacteria, BV molecular diagnostic tests, and novel treatment regimens. Additionally, recent literature on alcohol abstinence in the setting of 5-nitroimidazole use was reviewed.